MORALITY AND EMPLOYEE ENGAGEMENT IN ORGANIZATIONS - Dagogo, Tamunomiebi Miebaka; Roseline, Mills Bamidele (European Journal of Human Resource, 2020)
This study examined the relationship between morality and employee engagement in an organization. The approach adopted is theoretical as it assesses based on extant literature. The result of the study revealed that sound empirical conduct or moral behavior at work improves employee engagement and brings about organizational growth. Also, an improvement in workplace morals and ethical behavior improves employee engagement. Therefore, for the firm to upscale productivity, the organization should drive engagement through an objective ethical and moral behavior at work. It is recommended that management of organizations should have sound morals and ethical behavior, this will improve engagement. Again, organizations should put in place robust corporate governance system, this will guide workplace behavior and morals